Tractor engine load and fuel consumption in road construction works - Janulevičius, Algirdas; Juostas, Antanas; Pupinis, Gediminas (Transport, 2010)
Tractor load influences engine work parameters having an influence on the working economy and productivity of the complete tractor aggregate. The operational economy and productivity of the tractor is mostly evident when its engine power is utilized at least at 80% and engine speed is as low as possible. The paper analyses the engine parameters of tractor Massey Ferguson MF 8480 during the operational period of road construction works. Control tests on the parameters of the engine load of the tractor engine in combination with the employed milling equipment WS 2500 produced by the company ‘Wirtgen’ were performed. The study was carried out using engine load tables and graphs collected and stored in the so called ECU Load Profileintegrated in Electronic Engine Control Units. Theoretical analysis was made and an equation presented to establish the relation between engine power, engine speed and the quantities of cyclic fuel consumption. The study results present the distribution graphs of work time and fuel consumption at different engine speed during the operational period. The paper also indicates engine load and fuel consumption graphs of the tractor in combination with milling equipment. The article has also disclosed that the analysis of engine speed and load modes using information obtained from tractor‐integrated digital microprocessors reveals the operation quality of the tractor. First published online: 10 Feb 2011